A first-principles study of electronic and optical properties of the tetragonal phase of monolayer ZnS modulated by biaxial strain. Issue 10 (21st February 2022) - Liu, Bin; Su, Wan-Sheng; Wu, Bi-Ru
Abstract : The evolution of electronic property for monolayer tetragonal ZnS under biaxial strain. Abstract : Modulation of the electronic and optical properties of two-dimensional (2D) materials is of great significance for their practical applications. Here, by using first-principles calculations, we study a tetragonal phase of monolayer ZnS, and explore its associated electronic and optical properties under biaxial strain. The results from phonon dispersion and molecular dynamics simulation demonstrate that the tetragonal phase of monolayer ZnS possesses a very high stability. The monolayer ZnS has a direct band gap of 4.20 eV. It changes to an indirect band gap under both compression and tension, exhibiting a decrease in band gap. However, the band gap decreases more slowly under compression compared to the tension process such that the direct band gap remains within −8%, demonstrating excellent endurance under pressure. Fortunately, tetragonal ZnS exhibits a good absorption ability in the ultraviolet (UV) range regardless of strain. Our research results enrich the understanding of monolayer ZnS, which is helpful for the design and application of optoelectronic devices using the material.